NEOLIBERALISMO, IDEOLOGIA E PROCESSO: A FORMAÇÃO JUDICIAL EMANCIPATÓRIA COMO FATOR DE PROTEÇÃO AO DESENVOLVIMENTO SUSTENTÁVEL - Reis, Sérgio Cabral dos (Revista da AJURIS, 2016)
NEOLIBERALISM, IDEOLOGY E PROCEDURE: THE EMANCIPATORY JUDICIAL FORMATION AS FACTOR OF PROTECTION TO SUSTAINABLE DEVELOPMENT RESUMO: O processo, como meio do exercício da jurisdição estatal, nem sempre tem servido à efetiva tutela dos direitos, pois a ideologia hegemônica enraíza o seu paradigma de dominação em todas as instituições, o que inclui o Poder Judiciário. Para que o processo sirva de instrumento de solução adequada dos complexos dilemas e conflitos sociais pós-modernos, e, por consequência, caminhe em direito aos valores constitucionais do desenvolvimento sustentável, os juízes, emancipados a partir de uma formação crítica multidisciplinar, devem romper com o paradigma neoliberal hegemônico. PALAVRAS-CHAVE: Jurisdição; processo; ideológica; educação emancipatória; desenvolvimento sustentável. ABSTRACT: The procedure, as a way of exercise of State jurisdiction, has not always served the effective tutelage of rights, on this account, the hegemonic ideology, which roots the paradigm of domination in all institutions, what includes the judicial power. For the process to serve as a suitable solution tool for complex dilemmas and postmodern social conflicts, and, by consequence, walk according to the constitutional values of sustainable development, the judges, emancipated by a critical multidisciplinary formation, must break up with the hegemonic neoliberal paradigm. KEYWORDS: Jurisdiction; procedure; ideological; emancipatory education; sustainable development. SUMÁRIO: Introdução; 1 Neoliberalismo e desenvolvimento democrático sustentável; 2 Discurso ideológico: identificando a lógica do entrave ao desenvolvimento socioambiental; 3 A superação do discurso ideológico pela educação emancipatória; 4 Estado Democrático de Direito e desenvolvimento sustentável: a formação judicial interdisciplinar para romper com o plano formal; 5 Jurisdição e pós-positivismo: rompendo com o racionalismo liberal rumo à tutela judicial do desenvolvimento sustentável; Considerações finais; Referências. SUMMARY: Introduction; 1 Neoliberalism and sustainable democratic development; 2 Ideological speech: identifying the logic of obstacle to environmental development; 3 The overcoming of ideological speech by emancipatory education; 4 Democratic State and the sustainable development: the interdisciplinary judicial formation in order to break-up with the formal level; 5 Jurisdiction e post-positivism: breaking-up with the liberal rationalism towards judicial tutelage of sustainable development; Closing remarks; References.